MANAJEMEN PENDIDIKAN DALAM PERSPEKTIF ALQUR’AN - HASAN ZAINI (al-fikrah: Jurnal Manajemen Pendidikan, 2016)
Management of education in perspective al-Qur’an. The Qur'an is the way of life of all time, which is relevant in every time, place and situation . In the Qur'an not only discussed the matter of belief, worship, morals, halal and haram , but there are also issues of science. Among them about education issues, including the scope of Management Education. Word "Yudabbiru " which means set, can be used as the basis that the Qur'an there memamng discuss management ( setting ) of God to his creation , including arranging all the affairs of His creatures. This can be understood from the fact that man as a vicegerent of God on earth has the duty and obligation to manage, administer and prosperity of this earth . Education includes administering and managing well education Management is the foundation of Islam Qur'an and Hadith with the principle of Tauhid, Khalifah and trustful. Furthermore, the function of which is popularly called management Planning, Organizing, Actuating and Controlling, in line with the teachings of the Qur'an, that in life and life, man must have the planning , organization , unity and mutual cooperation. In addition it should also be able to move others to do good in the form of motivation, advice and guidance . Then needs to be controlled and monitored in order to get maximum results.Kata kunci:  Al-Qur’an, perspektif, manajemen pendidikan.